Tempora si fuerint nubila - Skubic, Mitja (Verba hispanica, 2013)
The Romance verb is, especially for linguists interested in questions of the syntax of the verb, and in particular in the values of verb paradigms for the past, a source of constant reflection. If for no other reason because Romance languages have, or used to have, a simple and a composed past tense form,which continue to be present at least in the use of careful speakers, although not to the same extent in all the languages: in some Romance areas, the simple past almost disappeared from everyday use, where as in others like southern Italy and the Iberian peninsula the simple past tense inherited from Latin isstill a heavily used verb form, as it is also in Sicilian, Portuguese and Castilian, at least in some dialects, and particularly in the New World.The article tries to capture the values of the composed past tense in some Romance literary works. The examples, some of which are from modern literary texts, prove that this verb form occasionally still retains its original value of the perfect tense and refers generally to an accomplished state, which implies that it can also be used to express a future or an extra-temporal state, and not only a present one. Such uses can be noticed in particular in the language of the theatre.
Keywords: romanski jeziki; glagol; verb; sestavljeni preteklik